A computational and experimental study of the cyclic voltammetry response of partially blocked electrodes. Part II: Randomly distributed and overlapping blocking systems - Davies, T; Brookes, B; Fisher, A; Yunus, K; Wilkins, S; Greene, P; Wadhawan, J; Compton, R (2003)
The cyclic voltammetric response of partially blocked electrodes is modeled using finite difference simulations, and a method is presented for the determination of currents at electrode surfaces that have an unstructured blocking pattern. The method is first applied to predict the current at purposely fabricated gold film electrodes in which monodispersed blocking disks are randomly sprinkled over the gold surface. The theoretical models are subsequently applied to the case of a basal plane pyrolytic graphite electrode modified with microdroplets of an electrochemically inactive oil. The theoretically predicted results are in good agreement with those observed experimentally.